2001
DOI: 10.1063/1.1373405
|View full text |Cite
|
Sign up to set email alerts
|

Raman scattering test of single-wall carbon nanotube composites

Abstract: Raman spectroscopy is used to infer elastic properties of single-wall carbon nanotubes (SWNTs) in composites. This letter presents strain-induced frequency shift of tangential Raman active modes of SWNTs embedded in epoxy resin subjected to bending. Epoxy curing and sample extension in the tensile strength test are found to create residual strains on the SWNT ropes. We demonstrate that specimen compression in combination with the Raman microprobe technique provides a means for determining of these strains and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

16
78
0
1

Year Published

2004
2004
2013
2013

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 141 publications
(95 citation statements)
references
References 13 publications
16
78
0
1
Order By: Relevance
“…Reports [4,8] that describe stress induced band shifts in the 9 Raman spectrum of SWCNTs in carbon nanotubes composites help to substantiate this theory.…”
Section: A Nanocompositesmentioning
confidence: 75%
See 3 more Smart Citations
“…Reports [4,8] that describe stress induced band shifts in the 9 Raman spectrum of SWCNTs in carbon nanotubes composites help to substantiate this theory.…”
Section: A Nanocompositesmentioning
confidence: 75%
“…Measurements were performed over temperatures in the range of 5 K to 400 K and at magnetic fields up to 1.5 Tesla. 4 Data reproducibility was checked by either repeating measurements on the same sample or conducting the same measurements on different samples from the same batch of SWCNTs. Data consistency was also obtained by comparing the results of temperature dependence measurements with those of magnetic field dependence.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…18 For CNT composites, it was reported that compressive strain can induce frequency shift of Raman G modes of SWNTs/ epoxy composites subjected to bending. 19 However, these studies relied on the measurements of bulk CNT materials and their composites in which the transfer of mechanical stresses and actual shape of the stressed CNTs remain unknown to great extent. Raman studies of bulk CNT materials demonstrated frequency upshift with increasing compressive strain under hydrostatic pressure.…”
mentioning
confidence: 99%